2009
DOI: 10.1111/j.1540-8167.2009.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fluoroscopy During Atrial Fibrillation Ablation: Benefits of Robotic Guided Navigation

Abstract: The use of RN for PVI seems to be effective and significantly reduces overall fluoroscopy time and operator's fluoroscopy exposure without affecting mid-term outcome after 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 13 publications
(17 reference statements)
6
62
0
5
Order By: Relevance
“…Special catheters with magnets affixed to their distal end can be navigated PV isolation reports in paroxysmal and persistent AF patients using the Sensei system have consistently shown significant shortening of the fluoroscopy time. [48][49][50][51][52] Remote isolation of the PV showed similar midterm follow-up (six-months to one-year) free of atrial arrhythmias to manual point-by-point radiofrequency delivery. Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 91%
See 2 more Smart Citations
“…Special catheters with magnets affixed to their distal end can be navigated PV isolation reports in paroxysmal and persistent AF patients using the Sensei system have consistently shown significant shortening of the fluoroscopy time. [48][49][50][51][52] Remote isolation of the PV showed similar midterm follow-up (six-months to one-year) free of atrial arrhythmias to manual point-by-point radiofrequency delivery. Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 91%
“…Further experience and introduction of a special feature of the system to indirectly estimate catheter contact force on the tissue (IntelliSense) have shown that tamponade rates are not greater than the conventional manual approach and may be more related to different temperature and power RF settings. 50,52 High incidence of oesophageal ulcerations has been reported by Tilz et al during PV isolation using 30 watts (W) along the posterior wall. The use of power limit to 20 W along the posterior wall in combination with an oesophageal temperature limit of 41 degrees Celsius significantly reduced the risk of oesophageal injury.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the beginning of interventional electrophysiology for diagnosis and therapy of cardiac arrhythmias, fluoroscopy techniques have been widely used to navigate catheters within the heart and the vessels and to monitor their position. In recent years, technical developments have led to the routine and wide-spread use of non-fluoroscopic three-dimensional (3D) electro-anatomical navigation and mapping systems for radiofrequency ablation (RFA) of tachyarrhythmias including atrial fibrillation (AF) resulting in a significant reduction of radiation dose during mapping and ablation of complex arrhythmias [7][8][9][10][11][12]. Minimizing the exposure to radiation is recommended by the American College of Cardiology teaching the ALARA principlekeeping the radiation "as low as reasonably achievable" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although X-ray doses used during fluoroscopy for AF ablation ( figure 3A) are often modest, novel imaging modalities have further reduced fluoroscopy exposure and even provide the ability to perform AF ablation without X-ray 93 . Robotic and magnetically guided catheters allow a reduction in irradiation to the operator while maintaining equivalent results to traditional systems 94 . A recent innovation is the use of a novel magnetic based tracking system combined with stored fluoroscopic images 95 that has further reduced the already low fluoroscopy times seen with contemporary mapping systems (figure 3B).…”
Section: Evolving Technical Aspects Of Ablation: Less Is Morementioning
confidence: 99%